A study on performance evaluation of mutual funds with reference to Cochin stock exchange Ltd - Varathan, Sathya; Vigneshwari, N; Tamilenthi, S (International Multidisciplinary Research Journal, 2012)
This study is an attempt to identify overpriced and underpriced shares chosen. It can be used as a guide for the investors to make a purchase or sell decision for a particular security. The sample of securities of 8 private sector banks were selected and using either anticipation approach to estimate the value of a shares are calculated. As per anticipation approach future price of a share is estimated through trend analysis which will be compared with actual share price on a particular date to find whether the share is underpriced or overpriced.